Technical Validation and Clinical Utility of an NGS Targeted Panel to Improve Molecular Characterization of Pediatric Acute Leukemia - Vicente-Garcés, Clara; Esperanza-Cebollada, Elena; Montesdeoca, Sara; Torrebadell, Montserrat; Rives, Susana; Dapena, José Luis; Català, Albert; Conde, Nuria; Camós, Mireia; Vega-García, Nerea (Frontiers in Molecular Biosciences, 2022)
Development of Next-Generation Sequencing (NGS) has provided useful genetic information to redefine diagnostic, prognostic, and therapeutic strategies for the management of acute leukemia (AL). However, the application in the clinical setting is still challenging. Our aim was to validate the AmpliSeqTM for Illumina® Childhood Cancer Panel, a pediatric pan-cancer targeted NGS panel which includes the most common genes associated with childhood cancer, and assess its utility in daily routine of AL diagnostics. In terms of sequencing metrics, the assay reached all the expected values. We obtained a mean read depth greater than 1000x. The panel demonstrated a high sensitivity for DNA (98.5% for variants with 5% variant allele frequency, (VAF) and RNA (94.4%), a 100% of specificity and reproducibility for DNA and 89% of reproducibility for RNA. Regarding clinical utility, 49% of mutations and 97% of the fusions identified were demonstrated to have clinical impact. Forty-one % of mutations refined diagnosis, while 49% of them were considered targetable. Regarding RNA, fusion genes were more clinically impactful in terms of refining diagnostic (97%). Overall, the panel found clinically relevant results in the 43% of patients tested in this cohort. To sum up, we validated a reliable and reproducible method to refine pediatric AL diagnosis, prognosis and treatment and demonstrated the feasibility of incorporating a targeted NGS panel into pediatric hematology practice.